Performance of the resolute zotarolimus‐eluting stent in small vessels. Issue 1 (7th April 2014) - Caputo, Ronald; Leon, Martin; Serruys, Patrick; Neumann, Franz‐Josef; Yeung, Alan; Windecker, Stephan; Belardi, Jorge A.; Silber, Sigmund; Meredith, Ian; Widimský, Petr; Saito, Shigeru; Mauri, Laura
Abstract : Background: Drug eluting stents for the treatment of small vessel coronary artery disease have traditionally yielded inferior clinical outcomes compared to the use of DES in large vessels. The benefit of the second‐generation Resolute zotarolimus‐eluting stent (R‐ZES) in small vessels was examined. Methods: Two‐year clinical outcomes from five combined R‐ZES studies were compared between patients with small (reference vessel diameter [RVD] ≤2.5 mm; n = 1, 956) and large (RVD >2.5 mm; n = 3174) vessels. Results: Despite a higher incidence of comorbidities in the small vessel group, there was no significant difference in target lesion failure (TLF) (10.1% vs. 8.7%; P = 0.54) at 2 years. When the subgroup of patients with diabetes was examined ( n = 1, 553) there was no significant difference in 2‐year TLF in small compared to large vessels (11.2% vs. 11.1%; P = 0.17). Similarly, within the small vessel cohort, no significant difference was seen regarding TLF at 2 years between people with and without diabetes (11.2% vs 9.6%; P = 0.28). Conclusion: When used for the treatment of small vessels, the R‐ZES appears to provide acceptable clinical results at 2 years when compared to its performance in large vessels. © 2014 Wiley Periodicals, Inc.